2021
DOI: 10.1038/s41467-021-22890-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune evolution from preneoplasia to invasive lung adenocarcinomas and underlying molecular features

Abstract: The mechanism by which anti-cancer immunity shapes early carcinogenesis of lung adenocarcinoma (ADC) is unknown. In this study, we characterize the immune contexture of invasive lung ADC and its precursors by transcriptomic immune profiling, T cell receptor (TCR) sequencing and multiplex immunofluorescence (mIF). Our results demonstrate that anti-tumor immunity evolved as a continuum from lung preneoplasia, to preinvasive ADC, minimally-invasive ADC and frankly invasive lung ADC with a gradually less effective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 74 publications
15
52
0
Order By: Relevance
“…S4c–d ). For example, the enrichment of T and B lymphocytes as well as the decline in natural killer (NK) cells and granulocytes during tumor progression, suggesting activation of adaptive immune responses, which is consistent with a previous report that immune evasion may have started as early as the preneoplastic stage 18 . These results illustrate a high level of transcriptomic heterogeneity within LUAD, could be at least partially modulated by the surrounding microenvironment during progression.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S4c–d ). For example, the enrichment of T and B lymphocytes as well as the decline in natural killer (NK) cells and granulocytes during tumor progression, suggesting activation of adaptive immune responses, which is consistent with a previous report that immune evasion may have started as early as the preneoplastic stage 18 . These results illustrate a high level of transcriptomic heterogeneity within LUAD, could be at least partially modulated by the surrounding microenvironment during progression.…”
Section: Resultssupporting
confidence: 91%
“…Transcriptional phenotypes in TMs, which are involved in apolipoprotein metabolism, are observed mostly in IA stage. Consistent with recent findings, these alterations in stromal and immune populations cooperatively transformed immune-competent tissues into an immune-suppressive TME during LUAD progression 18 , 48 , 61 . Eventually, we find that MDK and TIMP1 are potential biomarkers to facilitate our understanding of LUAD pathogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Clinical application of low-dose computed tomography (CT) has contributed to a substantial increase in the detection of pulmonary nodules and a reduction in mortality of lung cancer, however, the high false-positive rate of imaging highlights the need for potent approaches for early detection of high-risk patients 4 . Recent studies have depicted the genomic and immune landscape of these lesions and revealed the molecular events underlying the initiation and progression of LUAD 5 10 , which may facilitate early diagnosis and cancer prevention. However, deep insight into the metabolic trajectory from AAH to IAC remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the gene expression profiles of ADC in the development of lung cancer have been well investigated [ 12 , 13 ], relatively little is known about the global transcriptome changes associated with AAH [ 6 ]. Moreover, although recent studies have reported suppressed antitumor and enhanced protumor activities related to immune signaling in AAH, as well as sequential changes in immunity-related features across a continuum from preinvasive to advanced lung ADC [ 10 , 16 ], these results require further verification. However, due to the scarcity of tissue samples and the highly diverse genetic background of lung ADC, confirmatory studies are challenging.…”
Section: Introductionmentioning
confidence: 99%